Managing Cecal Enterocutaneous Fistula Through Application of Cecostomy Tube : an Effective Approach - Pattiiha, Abdul Muthalib; Kusmayadi, Dikki Drajat; Lia, Emiliana; Caesarini, Evelyn Franca (Syntax Corporation Indonesia, 2025)
One of the rare post appendectomy complications is enterocutaneous fistula in the cecum. There is limited research on surgical treatment for this condition; however, excising the fistula and performing primary closure with placement of a cecostomy tube could be considered as another potential approach. A 12-year-old boy who underwent appendectomy surgery 2.5 years ago presented with a complaint of fecal discharge from a surgical scar in the right lower abdomen, which began 7 days after the operation. He observed intestinal mucosa protruding from the enterocutaneous fistula opening two weeks prior to hospital admission. Fistulography revealed an enterocutaneous fistula in the right lower abdomen originating from the proximal ascending colon. During exploratory laparotomy, an enterocutaneous fistula was identified in the cecum, originating from the appendiceal stump. The fistula was excised, followed by primary suture and insertion of a cecostomy tube, positioned with its end 15 cm proximal to the ileocecal junction. The cecum was then fixed to the right lower abdominal peritoneal wall. The cecostomy tube was removed on the 14th day after surgery, and during follow-up, there were no signs of leakage or recurrence of the fistula. The management of fistulas involves both conservative and surgical approaches. In our instance, surgical intervention included excising the fistula and performing primary suture, along with inserting a cecostomy tube. This approach aimed to preserve the function of the cecum, thereby reducing pressure on it and facilitating decompression. This case is uncommon, and there is limited literature on its treatment. It necessitates personalized management. The use of a cecostomy tube could be considered as an alternative surgical approach in managing enterocutaneous fistulas involving the cecum.